Pengaruh Total Asset Turnover (TATO) dan Debt to Equity Ratio (DER) Terhadap Return On Assets (ROA) Pada Perusahaan Sub Sektor Healthcare Yang Terdaftar Di Bursa Efek Indonesia Periode 2021 – 2025. - Deviyani Ispriyanti; Niken Herawati (Sekolah Tinggi Ilmu Manajemen Indonesia YAPMI, 2026)
This study aims to determine the effect of Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) on Return on Assets (ROA) of healthcare sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2025. The population and sample of the study were 35 financial report data from 2021-2025. Data collection techniques were through observation and documentation studies in the form of secondary data, namely published financial reports. Data analysis used descriptive statistical tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that Total Asset Turnover has a partial positive and significant effect on Return on Assets with a t-value of 5.190 and a significance of 0.000. Debt to Equity Ratio has a partial negative and significant effect on Return on Assets with a t-value of -3.049 and a significance of 0.005. The results of the f-test obtained a significance value of 0.001 less than 0.05 and the calculated f-value of 15,708 is greater than the f-table of 3.29, which means that together Total Asset Turnover and Debt to Equity Ratio have a significant positive effect on Return on Assets.